2024
DOI: 10.1002/btpr.3428
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐omics kinetic analysis of recombinant adeno‐associated virus production by plasmid transfection of HEK293 cells

Min Lu,
Zion Lee,
Wei‐Shou Hu

Abstract: Recombinant adeno‐associated virus (rAAV) is among the most commonly used vectors for gene therapy. It is commonly produced by transfection of HEK293 cells with three plasmids each containing the vector genome including gene of interest (GOI), helper functions, and rep and cap genes for genome replication and capsid formation. To meet the potential clinical needs, the productivity of the production system needs to be enhanced. A better process characterization of the production system will further advance our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Nevertheless, in all three cases, regardless of whether the genome was wtAAV or rAAV, whether the viral components were encoded by virus, plasmid vector, or integrated genetic modules, the host cell responded in a broadly similar manner, invoking pathways in immune response, inflammation, and MAPK signaling pathways. The earlier study on omic dynamics of rAAV-DJ transfection system also found that functional classes in inflammatory and immune response as well as MAPK signaling were enriched (Lu et al 2024b ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, in all three cases, regardless of whether the genome was wtAAV or rAAV, whether the viral components were encoded by virus, plasmid vector, or integrated genetic modules, the host cell responded in a broadly similar manner, invoking pathways in immune response, inflammation, and MAPK signaling pathways. The earlier study on omic dynamics of rAAV-DJ transfection system also found that functional classes in inflammatory and immune response as well as MAPK signaling were enriched (Lu et al 2024b ).…”
Section: Discussionmentioning
confidence: 91%
“…A recent study reported the transcriptome and proteome dynamics of rAAV-DJ production by triple plasmid transient transfection of HEK293 cells (Lu et al 2024b ). Although that study used a different AAV serotype, we nonetheless plotted the data from that case along with the three cases from this study as shown in Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%